Do Male Managers Increase Risk-Taking of Female Teams? Evidence from the NCAA - René Böheim; Christoph Freudenthaler; Mario Lackner (Institute of Labor Economics (IZA), 2019)
We analyze the effect of the coach's gender on risk-taking in women sports teams using data taken from National Collegiate Athletic Association (NCAA) basketball games. We find that the coach's gender has a sizable and significant effect on risk-taking, a finding that is robust to several empirical strategies, including an instrumental variable approach. In particular, we find that risk-taking among teams with a male head coach is 5 percentage points greater than that in teams with a female head coach. This gap is persistent over time and across intermediate game standings. The fact that risk-taking has a significantly positive effect on game success suggests that female coaches should be more risk-taking.
Keywords: J16; J44; 330; corporate risk-taking; gender difference; success